Avaliação da satisfação dos usuários de sistemas integrados de gestão (ERP) nas médias empresas de confecção do vestuário de Fortaleza - Teles, Francismilton (2012)
The small and medium businesses are the majority on the national scene, generating jobs and income for the nation. One of the tools that help increase the competitiveness of these companies is the use of Integrated Management Systems (ERP), which, when used properly, assist in planning, management and control. It is very important to check the success of such systems in companies and one of the most widely accepted means of analyzing them is by evaluating the satisfaction of its users. This paper assesses the satisfaction of users of ERP systems in medium-sized manufacturing clothing in Fortaleza, one of the largest clothing from Brazil. The method used was the Survey Research, through which 117 users were interviewed in 25 companies and followed the evaluation model customized by Ely (2010), which are evaluated quantitatively the satisfaction of end users and key users of an ERP system . The results show, in general, users are satisfied with the ERP systems implemented. It was also verified by multivariate analysis, the model used was appropriate to the context of medium-sized enterprises, because the statistical tests (Cronbach's alpha, Bartlett's sphericity and KMO) scores were very reliable.